Exploring the World Series: South and Central America. (Chip Taylor Communications, 2009)
Highly Recommended! This is a colossal series that viewers will want to watch again and again; it is filled with insight, and the appeal of each destination is clearly defined. -CITC Review Filmed entirely on location, featuring world-famous attractions to lesser-known hideaways, various hosts and tour guides in this series provide you with an experienced insider's look at each destination, leaving you with a better understanding and deeper appreciation of the people you meet, the places you see, the histories you learn and the cultures you get absorbed in. Co-produced by Jake and Mieke DeBoer; updated by Chip Taylor. The series is divided into 6 geographic regions.